Freeze-thaw cycling under a calcium chloride environment: effects on CFRP strengthened concrete structures. (4th December 2006) - Boyajian, David M.; Ray, Indrajit; Davalos, Julio F.
The fracture mechanics specimen known as the Single Contoured-Cantilever Beam (SCCB) – an experimental approach designed to ascertain both qualitative and quantitative information about the integrity of Fibre Reinforced Polymer (FRP) laminate-to-concrete interface bonds – has been used to assess the detrimental effects of subjecting concrete structures externally strengthened with Carbon Fibre Reinforced Polymer (CFRP) sheets to a combined thermo-chemical environment involving Freeze-Thaw (FT) cycling under a calcium chloride (CaCl2 ) solution. Quantitative fracture measurements in terms of the Mode I critical strain energy release rates (GIc ) were recorded after 50, 100, 150, 200 and 300 cycles of alternate freezing and thawing; moreover, specimen weights and strains were measured initially and at the end of every 5th cycle. Considerable degradation of the interface bond integrity was found to have resulted, particularly for the latter-stage cycled beams.